Jonathan Yewdell Discusses Viral Immunology, Vaccine Development, Navigating a Scientific Career, and Offers Perspectives on Transforming Scientific Publishing and Research Education - Neil S. Greenspan (Case Western Reserve University, 2024)
In this interview, Jonathan Yewdell talks with Pathogens and Immunity senior editor Neil Greenspan about the evolution of viral immunology, highlighting his work and the contributions of other influential scientists. He emphasizes the importance of passion and collaboration in scientific research, illustrating the potential for groundbreaking discoveries through networking. He provides advice on navigating a scientific career, stressing the significance of strong mentorship. And he shares his perspective on transforming the scientific publishing industry and research education.